Improving Social Civilization. New Progress in Research on Perspective Taking in China - Tang, Linglong; Yang, Shaogang (ETHICS IN PROGRESS, 2024)
In recent years, in the journey of building a modern socialist country in the new era, perspective taking has gradually attracted the attention of Chinese scholars due to its contribution to improving social civilization and the adaptability of Chinese citizens to society. New perspectives and empirical research are constantly emerging, and scholars are constantly exploring and improving relevant theories while conducting research based on China’s own national conditions. In order to improve social civilization, they are exploring the specific development of Chinese citizens’ perspective selection, and starting to focus on the intervention and application of perspective taking ability, integrating research into various aspects of education, management, and other aspects of China’s modern social construction. In this essay, we explored the new research achievements of Chinese scholars in the past decade, focusing on the relationship between perspective taking and prosocial behavior, perspective taking and inter group relationships, perspective taking and management of special populations, and the impact of gender factors on perspective taking. It also provides inspiration for China to improve social civilization and solve corresponding social problems.